2013
DOI: 10.1002/grl.50487
|View full text |Cite
|
Sign up to set email alerts
|

Active blind thrusts beneath the Tokyo metropolitan area: Seismic hazards and inversion tectonics

Abstract: [1] The Tokyo metropolitan area, underlain by Neogene and Quaternary sediments more than 5 km thick, is currently deformed by blind thrusts that could generate hazardous earthquakes. However, their little geomorphic expression and dense urbanization make understanding of folds produced above them and recent deformation highly elusive. Here we show subsurface geometries of several active blind thrusts beneath this highly urbanized area, based on tectonic landforms, high-resolution seismic reflection data, and Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For example, a statistical analysis of crustal earthquakes in New Zealand has shown that more than half of the historical large earthquakes ruptured along previously unidentified faults 1 . Further cryptic and partly hidden active faults have also been documented at the Cascadia 68 , 69 margin as well as in the Kanto region of Japan 70 , and similar conditions are likely to exist along other subduction zones. We conclude that regional-scale acquisition of LiDAR topography, combined with the quantitative analysis of off-fault and on-fault geomorphic markers and geodetic data is a promising way forward that will ultimately improve our knowledge of the location, deformation mechanisms, and recurrence time of hitherto unidentified seismogenic faults at convergent margins.…”
Section: Resultsmentioning
confidence: 84%
“…For example, a statistical analysis of crustal earthquakes in New Zealand has shown that more than half of the historical large earthquakes ruptured along previously unidentified faults 1 . Further cryptic and partly hidden active faults have also been documented at the Cascadia 68 , 69 margin as well as in the Kanto region of Japan 70 , and similar conditions are likely to exist along other subduction zones. We conclude that regional-scale acquisition of LiDAR topography, combined with the quantitative analysis of off-fault and on-fault geomorphic markers and geodetic data is a promising way forward that will ultimately improve our knowledge of the location, deformation mechanisms, and recurrence time of hitherto unidentified seismogenic faults at convergent margins.…”
Section: Resultsmentioning
confidence: 84%
“…Such work may reveal the magnitudes and recurrence intervals of paleoearthquakes and allow a detailed assessment of the seismic hazards posed by these poorly understood thrust faults [Liu-Zeng et al, 2009]. Such work has been done for other active structures in convergent settings worldwide, such as in Los Angeles [Shaw and Shearer, 1999;Dolan et al, 2003] and Tokyo [Ishiyama et al, 2013]. Moreover, further refinement of 3-D structural models and community fault models for this region [Plesch et al, 2007] will be important in assessing seismic hazards.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, large earthquakes with recurrence intervals of several centuries to a few millennia can be missed by the use of temporally short datasets. As a consequence, geological records on centennial to millennial temporal scales and highresolution near-surface stratigraphic studies are crucial to understand the occurrence of large, but infrequent, seismic events (Begg et al, 1993;Sinha et al, 2005;Ishiyama et al, 2007Ishiyama et al, , 2013Dura et al, 2016).…”
Section: Introductionmentioning
confidence: 99%